A política nuclear brasileira até 1964 - Santos, Tomé Sudário Gomes Ferraz dos (2007)
This dissertation analyses a period of the Brazilian nuclear energy policy, from 1945 to the military coup of 1964. During this period Brazil sold a large amount of strategic minerals (thorium) to the United States and, although there was a national effort to control atomic energy, successive difficulties frustrated those expectations. Throughout the 20 years studied in this dissertation, it is possible to notice a strong American influence on the Brazilian nuclear policy, and the opposition between nationalistic tendencies (that intended to develop an independent nuclear technology in Brazil) and the tendencies that defended a dependency as regards the United States. It seems that the permanent conflict between those opposite forces contributed significantly to cause the downfall of the Brazilian nuclear program